Influence of Digital Manufacturing in Architecture. Constructive Processes in Collaborative Environments - Marín-Parra, Daniel (Corporación Universitaria del Caribe, CECAR., 2020)
Digital manufacturing methods have opened a new branch of reflection and creation for the Architecture of the XXI century. Today it is possible to tackle simple construction processes, without the need for advanced knowledge or specialized labor, as digital tools allow it. . This text seeks to reflect on the impact that digital manufacturing methods and open source design have generated on Architecture, through the construction of a self-supporting structure in Madrid, recognizing new trends and valuating the possible characteristics of a new Architecture focused on solve local problems.